Enzymatic polymerization of catechol under high-pressure homogenization for the green coloration of textiles - Su, Jing (2018)
Laccase from Myceliophthora thermophila was used to catalyze the polymerization of catechol under high-pressure homogenization for the green coloration of textile substrates. The oxidation reactions were conducted using different forms of laccase, namely native laccase, PEGylated laccase and PEGylated laccase immobilized onto an epoxy resin. The three enzyme forms were deposited inside a polyester fabric bag during the experiments. The amount of polymer obtained was similar when using the three enzyme forms and its dispersion in water/DMSO mixture lead to powder particles of about 3060nm. The immobilized and PEGylated enzymes lead to poly(catechol) with 13 and 10 units, respectively, while the native form gave rise to shorter polymers (DP=8). We have shown that the oxidation of catechol conducted under high-pressure homogenization can be an efficient methodology for the in situ coloration of textiles. The polymers produced by this methodology stained strongly the textile container, revealing this experimental set-up as a promising greener coloration/coating methodology involving milder conditions than the normally used in textile processes.